Time trade-off study to establish utility decrements in individuals with a spinal cord injury who perform intermittent catheterization. (31st December 2023) - Looby, A.; Davies, H.; Mealing, S.; Smith, A. B.; Avey, B.; Laezza, A.; Crossland, A.; Lane, E. F.; Ridler, M.; Cawson, M.
Abstract: Aims: To generate utility decrements for three attributes associated with catheterization for individuals with a spinal cord injury (SCI): the process of catheterization, the physical impact of urinary tract infections (UTIs) and worry associated with hospitalization. Materials and methods: Health state vignettes comprising various levels of the three attributes were developed. Two cohorts of respondents, corresponding to people with SCIs and a sample broadly representative of the UK population, were presented with nine vignettes (three vignettes for the mild, moderate and severe health states in addition to a random set of six vignettes). It was assumed no or a nominal decrement was associated with the mild health state. Utility decrements were derived from analysing the data obtained from the online time trade-off (TTO). A proportion of the SCI cohort ( n = 57) also completed the EQ-5D-5L questionnaire. Results: Utility decrements were generated using statistical models for the general population ( n = 358), the SCI population ( n = 48) and the two populations combined (merged model, n = 406). Results from the two cohorts showed minimal differences. For the merged model, SCI status was not statistically significant. All interaction terms, excluding SCI and the severe level of the physical attribute, were not statistically significant. Compared to the mild level, the greatest utility decrement calculated was the severe level of the emotional (worry) attribute (0.09, p < .001) for the SCI population. A significant decrement of 0.02 ( p < .001) was calculated for the moderate level of the emotional attribute for all models. The mean utility score for those with SCI having completed the EQ-5D-5L was 0.371. Limitations: Modest sample size of respondents from the SCI population ( n = 48). Conclusions: Worry associated with hospitalization had the greatest impact on patients' health-related quality of life (HRQoL). The catheterization process, such as the lubrication and repositioning of the catheter, also impacted on patients' HRQoL.